Are edger rolls useful to control the plate motion and camber in a reversing rolling mill?. (June 2022) - Pietschnig, Christopher; Steinboeck, Andreas; Kugi, Andreas
Abstract: In heavy-plate hot rolling, reversing rolling mills are typically used to reduce the thickness of steel slabs. Some reversing rolling mills are equipped with edger rolls to control the width of the rolled plate. At best, the straight plate centerline coincides with the lateral centerline of the rolling mill and the desired rectangular shape is exactly realized. In reality, lateral asymmetries like temperature gradients and thickness inhomogeneities cause a lateral movement, a camber, and a wedge-shaped cross section of the plate. These effects can reduce the product quality and entail collisions with the mill stand or other equipment along the roller table. To prevent this, active control of the lateral position and contour shape is desirable. In this work, a roughing mill where the roll gap adjustment is self-retaining, meaning that it can only be adjusted between rolling passes, is considered. As a control input during the rolling passes, the lateral position of the edger rolls is exploited. A mathematical model for both the lateral motion and the resulting shape of the plate is derived. The model is validated by measurement data recorded in an industrial plant. Based on the validated model, the question if edger rolls are useful to control the plate motion and shape is discussed. A two-degrees-of-freedom control concept composed of an optimization-based feedforward controller and a proportional feedback controller with Smith predictor is derived for the lateral motion and shape. The performance of the proposed control concept is demonstrated in simulation studies based on the validated model. Highlights: A detailed mathematical model for the lateral plate motion and the outgoing plate centerline in a reversing rolling mill is proposed. The model is validated by measurement data recorded in an industrial plant. The usefulness of edger rolls to control the camber in a reversing rolling mill is discussed. A two-degrees-of-freedom control concept is derived for the lateral motion and shape.